TH3.3: Addressing Gender Inequalities to Create More Climate-Resilient and Sustainable Food Systems - Bryan, Elizabeth; Alvi, Muzna; Huyer, Sophia; Ringler, Claudia (CGIAR GENDER Impact Platform, 2022)
Climate change affects every aspect of the food system, including all nodes along agri-food value chains from production to consumption. Men and women often have important contributions to make to address climate challenges within food systems; yet structural inequalities limit women's access to resources, services and agency and shape the ways in which men and women experience and are impacted by climate change. This background paper for the upcoming FAO Report on The Status of Rural Women in Agri-food Systems: 10 Years after the SOFA 2010-11, reviews the literature on gender, climate change and agri-food systems and finds strong evidence of gender inequalities in exposure and sensitivity to climate change, adaptive capacities, decision-making over alternative adaptive and policy responses, and well-being outcomes of climate change. It identifies a set of promising approaches to address these gender inequalities, including financial products tailored to women's needs, climate information services targeted to women, and group-based approaches for collective climate action. The review concludes that if climate-smart interventions do not adequately take gender differences into account, they might exacerbate gender inequalities in food systems. At the same time, women's contributions and agency are critical to make food systems more resilient to the negative impacts of climate change, given their specialized knowledge, skills and roles in agri-food systems. Thus, increasing the resilience of food systems to climate change requires inclusive approaches that build women's resilience capacities, facilitate women's empowerment, and address structural inequalities.